Meningkatkan Kemampuan Guru melalui Supervisi Akademik pada Masa Pandemi Covid-19 di SDN 2 Lenek Pesiraman Kecamatan Lenek - Ibrahim, Ibrahim (Lembaga Yasin AlSys, 2021)
The purpose of this school action research (PTS) is to find out the extent to which the supervision carried out by the principal followed by the provision of guidance/treatment to the target teachers can improve the teacher's ability to apply learning models in the classroom. In this school action research (PTS) it was conducted in 2 cycles, from the results of the actions taken it was proven to be able to improve the ability of teachers by achieving ideal standards. In the first cycle the teacher's ability to increase after classroom supervision was carried out after coaching on the use of new learning media reached about 33.33% in the second cycle it could increase to 100%. The average score obtained after class supervision in the first cycle was 69.67 and increased in the second cycle to 83.33, meaning that there was an increase of 13.66 and the group/classical level of completeness in the first cycle reached 33.33% and in the second cycle increased to 100%. The results of this school action research indicate that the coaching of school principals can improve the ability of teachers to use learning media in the learning process